Electrophysiological properties of rat nodose ganglion neurons co-transplanted with carotid bodies into the chick chorioallantoic membrane - Jaime Eugenín; Carlos Eyzaguirre (Biological Research, 2005)
The electrophysiological properties of nodose ganglion neurons were evaluated immediately after removing nodose ganglia from young adult rats and 3 to 10 days after nodose ganglia implantation _either alone or co-implanted with carotid bodies_ onto the chick chorioallantoic membrane. Implanted and co-implanted nodose neurons were less excitable than acutely recorded nodose neurons. Co-implanted neurons also showed reduced amplitudes for both action potentials and spike after-hyperpolarizations relative to those found in acutely recorded nodose ganglion neurons and a smaller time constant (τ) than that found in implanted neurons. In addition, no spontaneous activity was recorded from nodose ganglion neurons co-implanted with carotid bodies during 3-9 days, which suggests that functional synapses between carotid glomus cells and nodose neurons were not yet established. Results indicate the feasibility of obtaining viable nodose neurons for up to 10 days grafted onto the chick chorioallantoic membrane, where they can conserve most of their passive and active membrane properties and also are susceptible to carotid bodies trophic influences. They also suggest that nodose neurons would need more time for the development of functional synapses when grafted with carotid body glomus cells.